Comparing high-latitude thermospheric winds from Fabry–Perot interferometer (FPI) and challenging mini-satellite payload (CHAMP) accelerometer measurements - A. Aruliah; M. Förster; R. Hood; I. McWhirter; E. Doornbos (Annales Geophysicae, 2019)
It is generally assumed that horizontal wind velocities are independent of height above the F 1 region (> 300 km) due to the large molecular viscosity of the upper thermosphere. This assumption is used to compare two completely different methods of thermospheric neutral wind observation, using two distinct locations in the high-latitude Northern Hemisphere. The measurements are from ground-based Fabry–Perot interferometers (FPI) and from in situ accelerometer measurements onboard the challenging mini-satellite payload (CHAMP) satellite, which was in a near-polar orbit. The University College London (UCL) Kiruna Esrange Optical Platform Site (KEOPS) FPI is located in the vicinity of the auroral oval at the ESRANGE site near Kiruna, Sweden (67.8 ∘ N, 20.4 ∘ E). The UCL Longyearbyen FPI is a polar cap site, located at the Kjell Henriksen Observatory on Svalbard (78.1 ∘ N, 16.0 ∘ E). The comparison is carried out in a statistical sense, comparing a longer time series obtained during night-time hours in the winter months (DOY 300–65) with overflights of the CHAMP satellite between 2001 and 2007 over the observational sites, within ±2 ∘ latitude ( ±230 km horizontal range). The FPI is assumed to measure the line-of-sight winds at a height of ∼240 km, i.e. the peak emission height of the atomic oxygen 630.0 nm emission. The cross-track winds are derived from state-of-the-art precision accelerometer measurements at altitudes between ∼450 km (in 2001) and ∼350 km (in 2007), i.e. 100–200 km above the FPI wind observations. We show that CHAMP wind values at high latitudes are typically 1.5 to 2 times larger than FPI winds. In addition to testing the consistency of the different measurement approaches, the study aims to clarify the effects of viscosity on the height dependence of thermospheric winds.